1984
DOI: 10.1002/ajh.2830170103
|View full text |Cite
|
Sign up to set email alerts
|

Increase in density and accumulation of serotonin by human aging platelets

Abstract: 51Cr-labeled autologous platelets were infused into splenectomized subjects and the specific radioactivities of high-density (HD) and low-density (LD) platelet subpopulations were determined sequentially in postinfusion samples. A rapid decrease in the specific radioactivity of LD cohorts (T1/2 = 2.5 days) was observed, but the specific radioactivity of HD platelets remained constant or increased slightly during the first 4 days and then gradually declined for the next 5 days. No experimental artifacts during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 39 publications
3
11
0
Order By: Relevance
“…This view was more in line with that of Paulus that thrombopoiesis is likely responsible for platelet heterogeneity and not aging in circulation, but that only a single platelet population exists and the only size heterogeneity is that inherent to the log normally distributed population (25). Consistent with this thesis, other studies demonstrated that in the steady state platelet density does not change with circulatory age (26, 27), while others still showed that platelet density may increase with time due to accumulation of 5-hydroxytryptamine (5-HT) (28).…”
Section: Historical Perspectivessupporting
confidence: 58%
“…This view was more in line with that of Paulus that thrombopoiesis is likely responsible for platelet heterogeneity and not aging in circulation, but that only a single platelet population exists and the only size heterogeneity is that inherent to the log normally distributed population (25). Consistent with this thesis, other studies demonstrated that in the steady state platelet density does not change with circulatory age (26, 27), while others still showed that platelet density may increase with time due to accumulation of 5-hydroxytryptamine (5-HT) (28).…”
Section: Historical Perspectivessupporting
confidence: 58%
“…Since the platelet uptake rate depends on the 5-HT concentration in the surrounding plasma, generally, u i ( t 1 ) ≠ u i ( t 2 ). However, the 5-HT uptake and distribution of platelets appear to be little affected by their age or by how much 5-HT they have already accumulated [ 14 , 27 ]. Also, the numbers of platelets in blood vessels are very large and can be considered constant.…”
Section: Resultsmentioning
confidence: 99%
“…We observed that intraplatelet serotonin was decreased in patients with diffuse SSc compared with patients with limited SSc and healthy control subjects. Given that the serotonin content of platelets increases as platelets age in the circulation, this finding may be explained by a decreased platelet lifespan in the circulation with a consequent increased turnover in diffuse SSc [ 43 ]. However, this is also compatible with the notion of damaged endothelium-mediated platelet activation and accelerated removal of platelets from the circulation.…”
Section: Discussionmentioning
confidence: 99%